Blending, from English to Arabic - Mohsin, Ekhla Ali (Cambridge Scholars Publishing, 2021)
This book examines the interesting linguistic phenomenon of blending, where new words are formed to enrich the lexicon of a language. Blending in English has been thoroughly investigated to the extent that researchers and scholars refer to the results of these investigations when discussing this phenomenon in their respective languages. This book builds on existing studies by investigating blending in Arabic, and adopts a linguistic, systematic, and quantitative approach to discussing and analysing this process. It presents practical findings and prepares the road for further investigation in.